Type 2 diabetes mellitus and multiple chronic diseases - Nailya S. Asfandiyarova; Olga V. Dashkevich; Natalya V. Doroshina; Ekaterina I. Suchkova (Сахарный диабет)
Background: Recently, there has been an increase in the number of patients with multiple chronic diseases (MCD), particularly due to obesity and ageing. The role of type 2 diabetes mellitus (T2DM) in the development of MCD, however, is still unclear. Aims: This study aimed to determine the incidence of T2DM in the structure of polymorbidity considering sex and age-related characteristics. Materials and methods: Patients with MCD (n = 2,254; 769 men/1,485 women; aged, 18–99 years) were examined. The incidence of type 2 diabetes among patients with MCD considering age and sex was determined. Results: Type 2 DM was detected in 407 patients with MCD (18.1%; male:female, 1:2.53). The polymorbidity index in male patients with type 2 diabetes was 1.5–2.0 times higher than that in male patients without diabetes. The rate of polymorbidity index increase was similar in both groups; however, its high initial value in patients with diabetes at a young age determined the burden of the comorbidity at a later age. In type 2 diabetes, hypertension was the predominant comorbidity at 18–59 years of age (p<0.05), whereas other cardiovascular diseases and liver and kidney diseases were predominant at 45–74 years of age (p<0.001) and hemiplegia at 45–89 years of age (p<0.05). Between 60 and 74 years, oncological diseases were found to be more common in patients without diabetes (p<0.001). Obesity, regardless of the presence of diabetes, was associated with a greater disease burden (p<0.05). Sex-related difference considering MCD in patients with type 2 DM was only observed for the higher incidence of myocardial infarction (p<0.001) and peptic ulcer disease in males (p<0.01). Females were more likely to have obesity, liver steatosis at a young age, or osteoarthritis than males in the general group (p<0.05); no differences were noted with respect to other diseases. Conclusions: In this study, type 2 diabetes was present in 18.1% of patients with MCD; moreover, a high initial polymorbidity index in patients with T2DM at young age was associated with a higher incidence of chronic diseases later in life than that in patients without diabetes. Based on these results, type 2 diabetes, along with ageing and obesity, can be considered as a risk factor in the development of MCD.